The dimethyloxalylglycine-functionalized nanofibers for in situ regeneration of infected developing dental roots - Yeon Jee Yoo; Eun-Hye Lee; Jieun Bae; Woo Jin Kim; Chan Ho Park; Shin Hye Chung; Won Jun Shon; WooCheol Lee; Kyung Mi Woo (Materials Today Bio, 2025)
In situ regeneration in restorative dentistry targets the repair of tissues directly at the injury site by utilizing engineered biomaterials to guide endogenous cell activity. This approach aims to simplify treatment procedures and achieve more predictable outcomes, thus to supports the regeneration of damaged tissues and potentially restores tooth vitality, reducing the need for more invasive treatments. This study explores the potential of poly(ε-caprolactone) fibers (PCLF) functionalized with a hypoxia-inducible factor 1-alpha (HIF-1α) stabilizing small molecule dimethyloxalylglycine (DMOG) for in situ regeneration in the context of dental root repair in developing immature teeth. PCLF functionalized with DMOG (PCLF/DMOG) was applied to regenerative endodontic procedure (REP) treatment of infected developing dental roots, and its biologic properties and therapeutic potential were investigated through both in vitro studies and in vivo experiments, focusing on their capacity to promote in situ regeneration. In vivo application demonstrated the effectiveness of PCLF/DMOG in promoting root development, apical closure, and improving infectious lesions, contrasting with contemporary REP treatment controls that showed unpredictable outcomes. Mechanistically, the sustained release of DMOG from PCLF/DMOG significantly enhanced the expression of HIF-1α and upregulated expression of genes associated with angiogenesis and neurogenesis, including VEGF-α and NGF. The PCLF/DMOG upregulated antimicrobial peptides, facilitated efferocytic activities, promoted macrophage polarization to the M2 phenotype, and mobilized mesenchymal stem cells. Taken together, PCLF/DMOG could enhance innate immune responses and foster favorable microenvironment to guide cellular differentiation, promoting in situ regeneration of dental roots in the inflammatory microenvironments.